THE EFFECT OF ACTIVE AND FUNCTIONAL EXERCISE TO IMPROVE FITNESS, BALANCE AND FLEXIBILITY IN ELDERLY - Cerika Rismayanthi; Yudik Prasetyo; Tri Ani Hastuti (MEDIKORA, 2023)
The elderly will become vulnerable, apart from not being equipped with basic knowledge of specific physical activities to overcome the storm of aging symptoms, especially if psychological support is very lacking, this will clearly burden the body and soul of the elderly. Innovation in physical exercise models for the elderly needs to bridge the void of varied exercise in suppressing aging which is a healthy spirit for the elderly. This study investigate how innovations in the influence of active and functional exercise can have a positive influence on reducing symptoms of degenerative diseases. Method: The research used a pre test and post test design. Instruments for measuring fitness include 30 second-Chair stand (number of stands), Chain Sit Reach (inches +/-), Back Scratch (inches +/-), 8-Foot Up Go (seconds). Analysis of statistical data calculations using normality, homogeneity and paired t-test. The effect of active training and functional exercise which aims to improve fitness (strength and balance) so that the elderly are motivated to do physical exercise with exercise levels that are appropriate to the elderly's abilities. Development of an exercise model that is carried out with light-moderate intensity, duration/time of exercise is not too long, only around 20 to 30 minutes, exercise intensity is light, very simple movements are carried out in three positions, namely sitting, standing and lying down (supine and prone). The training model carried out is also a form of coordination that is close to daily activities. The physical training model, active training and functional exercise, is stated to have an effect on improving physical fitness (with the results of data analysis with the help of SPSS. Based on the results of the paired t test and Wilcoxon, the overall p value (sig.) for all variables is 0.000. The significance value is 0.000 0.05, then there is a significant influence. Active and functional exercise models have been proven to have an effect on improving physical fitness. Active and functional exercise models are effective for improving physical fitness for the elderly.